An updated patent review on P-glycoprotein inhibitors (2011-2018). (3rd June 2019) - Leopoldo, Marcello; Nardulli, Patrizia; Contino, Marialessandra; Leonetti, Francesco; Luurtsema, Gert; Colabufo, Nicola Antonio
ABSTRACT: Introduction : P-glycoprotein is a complex ATP-ase transporter involved in physiological and pathological functions. In particular, it is involved in the onset of multidrug resistance in cancer, in ocular disease, Chronic Rhinosinusitis, CNS diseases such as Alzheimer, Parkinson, and epilepsy. One of the aims of clinicians and pharmacologists is to monitor P-gp activity through the inhibitors and to use its activity and/or expression in physiological barriers for the early diagnosis of several pathologies. Considering P-glycoprotein activity, several substrates have been characterized but the challenge is to design ' pure ' P-glycoprotein inhibitors. Area covered : P-glycoprotein inhibitors display a large spectrum of activities. Here the contents of patents focused on the role of P-glycoprotein inhibitor in modulating MDR in cancer, in bioavailability, in ocular disease and Chronic Rhinosinusitis are reported. Expert opinion : the use of P-glycoprotein inhibitor sic et simpliciter, or in coadministration with therapeutic agents, for ocular disease, and Chronic Rhinosinusitis is promising and could be suggested for additional trials. By contrast, the bioavailability of the coadministrated drugs, increased by P-glycoprotein inhibitor, deserves a wider discussion, in particular on the pharmacokinetic aspect of both P-glycoprotein inhibitor and the coadministered drug.